2010
DOI: 10.1089/ten.tea.2009.0504
|View full text |Cite
|
Sign up to set email alerts
|

A Collagen–Chitosan Hydrogel for Endothelial Differentiation and Angiogenesis

Abstract: Cell therapy for the treatment of cardiovascular disease has been hindered by low cell engraftment, poor survival, and inadequate phenotype and function. In this study, we added chitosan to a previously developed injectable collagen matrix, with the aim of improving its properties for cell therapy and neovascularization. Different ratios of collagen and chitosan were mixed and chemically crosslinked to produce hydrogels. Swell and degradation assays showed that chitosan improved the stability of the collagen h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
5
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 35 publications
6
111
5
3
Order By: Relevance
“…The rheological properties of the collagen matrix were measured using a Brookfield R/S Plus Rheometer as previously described (Deng et al, 2010). Samples of collagen matrix or microsphere-collagen matrix (1.5 mL) were subjected to a constant shear rate of 5 s -1 for 20-30 min using a C50-2 spindle (spindle gap of 4 μm, according to the spindle specifi cations), and the temperature was maintained at 37 °C.…”
Section: Rheologymentioning
confidence: 99%
“…The rheological properties of the collagen matrix were measured using a Brookfield R/S Plus Rheometer as previously described (Deng et al, 2010). Samples of collagen matrix or microsphere-collagen matrix (1.5 mL) were subjected to a constant shear rate of 5 s -1 for 20-30 min using a C50-2 spindle (spindle gap of 4 μm, according to the spindle specifi cations), and the temperature was maintained at 37 °C.…”
Section: Rheologymentioning
confidence: 99%
“…[8][9][10] This has resulted in a wide variety of hydrogels developed from both synthetic and naturally derived polymers. 6,[11][12][13] Interestingly, both cell fate and cell function can be influenced by the hydrogel microenvironment. [14][15][16] Thus, ideally the hydrogel microenvironment should mimic the mechanical and biological demands and requirements of the tissues being replicated.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Typically, collagen and chitosan, alone or in combination, are crosslinked using exogenous, sometimes toxic, chemical crosslinkers to improve the hydrogel mechanical properties. 4,10,11 However, we have previously shown that chitosan-collagen composites gel because of ionic interactions at physiological temperature and pH to form mechanically stable hydrogels that are appropriate for in vivo application.12 Furthermore, the collagen-chitosan interaction within the gels resembles the collagen-glycosaminoglycan interaction found in vivo in the extracellular matrix. 13 Thus, chitosan-collagen may mediate physiological cell-matrix interactions.…”
mentioning
confidence: 99%